Konstruksi Pembentukan Identitas Kampung Digital Samirono - Endang Supriadi (Jurnal Sosiologi Agama, 2015)
This paper describes how identity construction carried outby the Kampung DigitalSamirono communities that are part ofthe Kampung Digital program. Because it Samirono villagewhich is known as the hometown of Javanese culture that stillretains the "KluwungBudaya Kampung" in the midst ofmodernization today, and people are dynamic, creative,innovative, and even has a rural and urban character. Samironocommunities who live in the era of modernization certainly willmake their identity is lost in the presence of the KampungDigital, but Samirono community can maintain their traditionsand identity in the presence of Kampung Digital. The presence ofthe Kampung Digital is providing a new color for the peopleSamirono, in which can`t be separated from the actors whohave the power in the formation of identity for the communitySamirono.the presence of the Kampung Digital communitySamirono have two different attitudes; First, accept that it isrepresentative of the Kampung Digital providers andgovernment programs. Second, consider the normal presence ofthe Kampung Digital, because it only benefits one party only (nomonopoly) because there are interests that dominate in theprogram. Then the actors in shaping the identity of the villagecommunity Samirono authorities (government) and companies(telkom).The government's role in disseminating the KampungDigital program in the villages especially Samirono and evenhas the authority in the implementation of the program. Thenthe role of the company positioned itself as superior to localproviders Samirono inferiority.Both are external factors that aredominant in constructing identity Samirono villagers. Thus theprocess of identity formation in SamironoKampung Digital is notindependent of external factors (providers and government),then formed a values, norms, and customs of the peopleSamirono.Keywords: Community Samirono, Construction of Identity,Kampung Digital.